Deel van de tentoonstelling naar aanleiding van het 40-jarig jubileum van SDAP. Schema van "de rode familie" (1934)
Deel van de tentoonstelling naar aanleiding van het 40-jarig jubileum van SDAP. Schema van "de rode familie"